The use of the "EUR-Lex" website for retrieving European legislation related to veterinary medicine - ANGELIDIS (Α.Σ. ΑΓΓΕΛΙΔΗΣ) A. S.; CHAINTOUTIS (Σ. ΧΑΪΝΤΟΥΤΗΣ) S.; TYRPENOU (Α.Ε. ΤΥΡΠΕΝΟΥ) A. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
This article contains instructions in the form of a "user’s manual" for the use of the "EUR-Lex" web site, which is the official European Union site for access to the European Union legislation. Anyone having access to the internet can conduct searches using the "EUR-Lex" website and retrieve results pertaining to the European Union legislation, such as Regulations, Decisions and Directives. This article contains descriptions of the different ways and approaches for conducting searches as well as descriptions and directions on evaluating and further handling the search results. The use of the "Eur-Lex" web site is free of charge (no subscription is necessary). The "Eur-Lex" site is undoubtedly the easiest and most direct tool for accessing the European Legislation in force and constitutes an invaluable resource for veterinarians, who wish to keep up to date with European Union legislation pertaining to all aspects of Veterinary Medicine.